2006
DOI: 10.1097/01.smj.0000215639.59563.83
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Delayed Initiation of HIV Medical Care Among Infected Persons Attending a Southern HIV/AIDS Clinic

Abstract: Background-Despite the proven benefits conferred by early human immunodeficiency virus (HIV) diagnosis and presentation to care, delays in HIV medical care are common; these delays are not fully understood, especially in the southern United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 68 publications
(44 reference statements)
2
55
1
Order By: Relevance
“…* In response, several organizations (e.g., AAHIVM, HIV Medicine Association, the AIDS Education and Training Centers Program of the Ryan White CARE Act, HealthHIV) have increased their efforts to: (1) draw students and clinicians into HIV medicine and increase provider diversity, (2) advocate for HIVrelated loan repayment programs and provider reimbursement changes, and (3) provide up-to-date clinical training for primary care providers. Finally, the geographic distribution of clinicians must also change in response to the evolving epidemic as infections continue to increase in medically underserved rural and innercity areas and the South (Figure 2)-regions where patients often delay care [32][33][34] and HIV treatment centers have difficulty recruiting and retaining providers. 27 * Some studies have found that provider gender and race affect patient satisfaction and health service utilization.…”
Section: Changing Providers: New Responsibilities Impending Shortagesmentioning
confidence: 99%
“…* In response, several organizations (e.g., AAHIVM, HIV Medicine Association, the AIDS Education and Training Centers Program of the Ryan White CARE Act, HealthHIV) have increased their efforts to: (1) draw students and clinicians into HIV medicine and increase provider diversity, (2) advocate for HIVrelated loan repayment programs and provider reimbursement changes, and (3) provide up-to-date clinical training for primary care providers. Finally, the geographic distribution of clinicians must also change in response to the evolving epidemic as infections continue to increase in medically underserved rural and innercity areas and the South (Figure 2)-regions where patients often delay care [32][33][34] and HIV treatment centers have difficulty recruiting and retaining providers. 27 * Some studies have found that provider gender and race affect patient satisfaction and health service utilization.…”
Section: Changing Providers: New Responsibilities Impending Shortagesmentioning
confidence: 99%
“…Because young people aged 15-24 years were least likely to have delayed diagnosis 18 and prevalence of viral suppression (13%) was lowest among those aged 18-24 years, 19 the higher risk of progression to AIDS largely suggests a lack of adequate access to care or adherence to HIV treatment among young people living with HIV. 1,[20][21][22][23] Higher risks of progression to AIDS and death among males with infection attributed to IDU or heterosexual contact, and among females with infection attributed to IDU, might be due to delayed diagnosis, 1 delayed linkage to HIV medical care, 1,24,25 less use of health services among heterosexuals and those who inject drugs, 14,26 and high-risk lifestyle factors or death from comorbidity conditions such as hepatitis C coinfection among people who inject drugs. 27,28 Observed disparities in the risks of progression to AIDS and death among people of multiple races and African Americans might reflect the disparities in delayed diagnosis, 18 access or linkage to medical care, 26 adherence to treatment, 22 and other socioeconomic factors that might affect access to HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…1,[20][21][22][23] Higher risks of progression to AIDS and death among males with infection attributed to IDU or heterosexual contact, and among females with infection attributed to IDU, might be due to delayed diagnosis, 1 delayed linkage to HIV medical care, 1,24,25 less use of health services among heterosexuals and those who inject drugs, 14,26 and high-risk lifestyle factors or death from comorbidity conditions such as hepatitis C coinfection among people who inject drugs. 27,28 Observed disparities in the risks of progression to AIDS and death among people of multiple races and African Americans might reflect the disparities in delayed diagnosis, 18 access or linkage to medical care, 26 adherence to treatment, 22 and other socioeconomic factors that might affect access to HIV care. 20,21,26,29 In addition, the higher risks of progression to AIDS and death in the South may reflect their delayed access to HAART or decreased likelihood of using HAART.…”
Section: Discussionmentioning
confidence: 99%
“…Aer the �rst six months of ART, this same association was only found at the 12-month time point ( ) (Table 2). 18,20) and the difference between these times was statistically signi�cant (log-rank, ) ( Figure 1). Statistically signi�cant difference between patients having baseline OL and those without baseline OL in the strati�ed analysis (baseline viral load 10,000 copies/mL group versus baseline viral load ≥10,000 copies/mL group) (log-rank, ) was also found.…”
Section: Oral Lesions Mirroring Viral Load Burden At Baseline and 12mentioning
confidence: 99%
“…e same proportions were calculated at 6, 12, 18, and 24 months. e nearest value to the end of each period (6,12,18, and 24 months aer initial visit) was recorded.…”
Section: Statistical Analysesmentioning
confidence: 99%